Proceedings. 2001 IEEE International Symposium on Information Theory (IEEE Cat. No.01CH37252)
DOI: 10.1109/isit.2001.936074
|View full text |Cite
|
Sign up to set email alerts
|

Low rate turbo-Hadamard codes

Abstract: Abstract-This paper is concerned with a class of low-rate codes constructed from Hadamard code arrays. A recursive encoding principle is employed to introduce an interleaving gain. Very simple trellis codes with only two or four states are sufficient for this purpose, and the decoding cost involved in the trellis part is typically negligible. Both simulation and analytical results are provided to demonstrate the advantages of the proposed scheme. The proposed scheme is of theoretical interest as it can achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 13 publications
0
48
0
Order By: Relevance
“…Regarding complexity, Table II shows the number of operations of a rate 1/7.7 layered LDGM scheme and the Turbo‐Hadamard code with the same rate from Reference 7. Although the number of exponential operations in the proposed scheme is larger than that of those based on Turbo‐Hadamard codes, there exist approximations for the decoding of parity checks that provide substantial reductions in complexity while keeping practically the same performance 22.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding complexity, Table II shows the number of operations of a rate 1/7.7 layered LDGM scheme and the Turbo‐Hadamard code with the same rate from Reference 7. Although the number of exponential operations in the proposed scheme is larger than that of those based on Turbo‐Hadamard codes, there exist approximations for the decoding of parity checks that provide substantial reductions in complexity while keeping practically the same performance 22.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…It is natural then to substitute the concatenation of code plus spreading by a single low‐rate code. In Reference 5, the use of Turbo‐Hadamard 7 codes is proposed, showing that the obtained performance is better than that of a conventional medium‐rate Turbo code concatenated with a spreading operation.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, R, I 118 and the low-rate turbo-Hadamard code [4] can be used. A turbo-Hadamard code with M constituent codes has an overall rate of r / ( r + M ~( 2 ' -r ) ) [4], where r is the order of the Hadamard code used. We transmit the information sequence, Rayleigh fading channels.…”
Section: Numerical Results Let Ninfo Be the Number Of Information Bitmentioning
confidence: 99%
“…Thus, a low-rate code can be used as C to maximize the coding gain. A good choice is the turbo-Hadamard code studied in [4] that can achieve performance close to the ultimate Shannon limit of -1.6dB in AWGN.…”
Section: Transmiper and Receiver Principlesmentioning
confidence: 99%
“…This approach has been successfully implemented for traditional multiple access schemes such as TDMA, FDMA or CDMA. In fact, similar near optimum FEC codes such as turbo-Hadamard codes [3] or low-rate turbo codes [4] have been used in the context of IDMA as well. On the other hand more recently, it has been shown that the proper choice of FEC for IDMA or SCMA should be a function of the number of users or the aggregate throughput [5].…”
Section: Code Design and Performance Of Scmamentioning
confidence: 99%